2014
DOI: 10.1177/1024258914526101
|View full text |Cite
|
Sign up to set email alerts
|

Multinationals and regional economies: embedding the regime shoppers?

Abstract: In a context in which multinational companies are increasingly able to choose their locations of production, this paper examines how social and political governance actors in host regional economies attempt to attract and retain foreign direct investment. Based on a comparative study of two regions in each of Canada, Ireland, Spain and the UK, it shows both national and in some cases sub-national variations in the nature of attempts to attract and retain foreign investment, as well as in the actors involved. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Nevertheless, within Spain, from the 1990s onwards, the state began to expand these new institutional roles in terms of labour relations representation and intervention. At the regional and autonomous government level the role of local state bodies in facilitating inward investment and longer-term planning did see a space for social dialogue in some aspects (Almond et al, 2014).…”
Section: Constructing the Public Sphere In The Realm Of Work And Emplmentioning
confidence: 99%
“…Nevertheless, within Spain, from the 1990s onwards, the state began to expand these new institutional roles in terms of labour relations representation and intervention. At the regional and autonomous government level the role of local state bodies in facilitating inward investment and longer-term planning did see a space for social dialogue in some aspects (Almond et al, 2014).…”
Section: Constructing the Public Sphere In The Realm Of Work And Emplmentioning
confidence: 99%
“…Power asymmetries favouring MNEs, increasing competition for FDI and its greater governance complexity, can lead to problems maximizing spillovers and the corporate capture of domestic institutions (Phelps and Fuller 2000;Phelps and Wood, 2006;Coffey and Tomlinson, 2006;Phelps, 2008;Christopherson and Clark, 2009;Almond et al, 2014;Driffield et al 2015). Recently, research has also stressed how local Inward Investment Regimes (IIRs) 'translate' MNE investment and influence cluster spillovers (Phelps and Wood, 2006;Driffield et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, FDI 'global pipelines' can stimulate clusters (Bathelt et al, 2004). MNEs can increase skilled labour stock, while regional institutions supporting training, learning and positive labour relations can reduce MNE 'regime shopping' (Almond et al, 2014). Yet, FDI can also undermine clusters by internalizing local assets (Rutherford and Holmes, 2008;Phelps, 2008).…”
mentioning
confidence: 99%
“…I compared different literature streams to confront the argument that institutional embeddedness is a key determinant. While most of the research about actors' embeddedness has focused on MNCs, their subsidiaries and managers (Almond, 2011;Almond et al, 2014;Kristensen and Zeitlin, 2005;Morgan and Kristensen, 2006), I have suggested that this embeddedness could also relate to trade unions and reinforce their strategies towards economic change. I have proposed two alternative explanations: these strategies may be shaped, first through power resources and capabilities (Lévesque and Murray, 2010) or second, through contingencies related to organizational characteristics of MNCs (Lippert et al, 2014;Pulignano and Stewart, 2012).…”
Section: Conclusion: Two Scenariosmentioning
confidence: 99%
“…Hence firms can play locations against one another in attempts to erode working conditions. In addition, Almond et al (2014) have shown that regions and their institutional specificities can 'embed' MNCs and attract investment; MNCs also become 'resource shoppers' looking for specific assets that regional contexts can offer. In deploying such assets in terms of skills, training, transportation or financial incentives, regions can become 'sticky places' (Markusen, 1996) in attracting FDI.…”
Section: Trade Unions and Corporate Restructuringmentioning
confidence: 99%